2005
DOI: 10.1118/1.1997765
|View full text |Cite
|
Sign up to set email alerts
|

SU‐FF‐T‐94: Clinical Evaluation of Direct Machine Parameter Optimization Algorithm for Head and Neck IMRT Treatment

Abstract: Purpose: Because many critical structures are in close proximity to target volumes, cancers of the head and neck (H&N) are often suited for treatment with IMRT. However, the time required to generate and deliver a clinically acceptable IMRT plan can be significantly longer than a conventional plan. This study evaluated a new inverse planning algorithm, DMPO (direct machine parameter optimization), with attention to parameter settings, plan quality and treatment efficiency for H&N cancers. Method and Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Such approaches are currently used in the field of IMRT, where optimization of fluence patterns for dose delivery is constrained by the shape and design of beam-shaping collimator leaves, via direct machine parameter optimization (DMPO). 49,50 A similar multileaf collimation approach for altering fluence patterns might also be applicable to FFMCT. Current MeV CT scanners for example, are already equipped with a multileaf collimation for dose delivery application.…”
Section: Discussionmentioning
confidence: 99%
“…Such approaches are currently used in the field of IMRT, where optimization of fluence patterns for dose delivery is constrained by the shape and design of beam-shaping collimator leaves, via direct machine parameter optimization (DMPO). 49,50 A similar multileaf collimation approach for altering fluence patterns might also be applicable to FFMCT. Current MeV CT scanners for example, are already equipped with a multileaf collimation for dose delivery application.…”
Section: Discussionmentioning
confidence: 99%
“…[6]. In addition, a clinical study has found that DSS optimization simplifies plans without reducing plan quality, compared to plans generated with the two-step approach [26]. Our segment generation module is based on the column generation approach for IMRT presented in [22].…”
Section: Introductionmentioning
confidence: 99%
“…Because of limitations of the MLC settings the resulting fluence is different from the optimization result and therefore no longer optimal [ 15 ]. Other systems incorporate the MLC sequencing in the optimization process [ 16 , 17 ], or optimize the machine parameters directly [ 18 , 19 ]. In both cases the MLC position is taken into account in the optimization process and the resulting optimal fluence can be delivered by the linac without further approximations [ 15 ].…”
Section: Introductionmentioning
confidence: 99%